A study on the usage of the Africana collection at the Kenneth Dike Library, University of Ibadan, Nigeria (2012)
This study examined the usage of Africana collection in Kenneth Dike Library of University of Ibadan. The collection is unique for its Africana content due to the responsibilities bestowed on it by the Nigerian legal deposit statutes. The research design adopted for this study was ex-post-facto study. The records of consultation kept in the Reference section of Kenneth Dike Library from 2009 to 2011 and statistics taken when there was relative stability in the academic calendar served as data. A qualitative analysis of data using frequencies and percentages was used to examine the usage of Africana collection and it showed that postgraduate students constitute the major users of the collection while library staff members are the least user-group. Theses and dissertations are the main resources consulted by all categories of users. The challenges faced in developing the collection include: lack of preservation policy, inadequate funding, shortage of staff, lack of space and harsh environmental conditions.